Development and evaluation of sildenafil/glycyrrhizin-loaded nanofibers as a potential novel buccal delivery system for erectile dysfunction - Ali A. Alamer; Abdullah A. Alshehri; Alhassan H. Aodah; Fahad A. Almughem; Hamzah A. Alghmadi; Amer S. Alali; Abdulrahman A. Halwani; Mohammed Muqtader Ahmed; Essam A. Tawfik (Elsevier, 2024)
Erectile dysfunction (ED) is a growing health condition that needs safe and effective therapy. One of the main common treatments is sildenafil which is used in clinics for managing erectile dysfunction by enhancing the blood supply to the penis. In the current study, sildenafil was formulated as nanofibers and mixed with the root extract of Glycyrrhiza glabra (glycyrrhizin) as a natural sweetener to be administrated in the buccal cavity for enhanced drug bioavailability, rapid drug absorption and improved patient compliance. The formulated dual-loaded nanofibers were evaluated by measuring diameter, disintegration, drug loading efficiency, drug release profile, and in vitro cell viability assessment. The results showed that the sildenafil/glycyrrhizin-loaded fibers had a diameter of 0.719 ± 0.177 μm and lacked any beads and pores formation on their surfaces. The drug loading and encapsulation efficiency for sildenafil were measured as 52 ± 7 µg/mg and 67 ± 9 %, respectively, while they were 290 ± 32 μg/mg and 94 ± 10 %, respectively, for glycyrrhizin. The release rate of sildenafil and glycyrrhizin demonstrated a burst release in the first minute, followed by a gradual increment until a complete release after 120 min. The in vitro cell viability evaluation exhibited that the application of sildenafil and glycyrrhizin is safe upon 24-hour treatment on human skin fibroblast cells at all used concentrations (i.e., ≤ 1,000 and 4,000 μg/mL, respectively). However, the application of sildenafil-glycyrrhizin combination (in a ratio of 1:4) demonstrated more than 80 % cell viability at concentrations of ≤ 250 and 1000 μg/mL, respectively, following 24-hour cell exposure. Therefore, sildenafil/glycyrrhizin dual-loaded PVP nanofibers showed a potential buccal therapeutic approach for erectile dysfunction management.